Performance of Synchronous Reluctance Generators with Series and Shunt Stator Connections - Obe, Pauline Ijeoma; Amuhaya, Lilian Livutse; Obe, Emeka Simon; Zungeru, Adamu Murtala (International Journal of Electrical and Computer Engineering Systems, 2023)
This paper reports the performance of series- and shunt-connected self-excited reluctance generators (SERG). In addition to the two stator connections, an analysis was carried out on rotor configurations (with and without a cage) a combination resulting in four different generator topologies. The loss of load and transient characteristics of each generator configuration were studied for a combination of pure resistive and R-L loads. It is shown that for the same machine size, speed and exciting capacitor value, the generator with a cage preserves a better wave shape following a transient disturbance than the cageless machine. At unity power factor, shunt generator with cage can deliver 0.691pu output power, at 1.97% regulation; its series counterpart only delivers 0.589 pu at 2.05%. The study demonstrates that while shunt generators have better regulation and supports higher loads at different power factors, series generators show a superior performance in terms of damping out transients.